2013
DOI: 10.1037/prj0000022
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effectiveness of an automated telehealth intervention to improve illness self-management in people with serious psychiatric and medical disorders.

Abstract: Objective Effective monitoring and treatment are needed to address the elevated rates of medical comorbidity among individuals with serious mental illnesses. This study examined the feasibility and potential effectiveness of an automated telehealth intervention, supported by nurse health-care management, among adults with serious mental illnesses and chronic medical conditions. Methods We conducted a single-arm pilot trial with 70 individuals with serious mental illnesses and chronic medical conditions who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 71 publications
0
33
0
1
Order By: Relevance
“…Among these were 4 modified versions of the Health Buddy automated home messaging device delivered across diverse mental health settings (Godleski et al, 2012; Kasckow et al, 2011; Pratt et al, 2013; Pratt et al, 2014), 3 separate evaluations of the Information Technology Aided Relapse Prevention Programme in Schizophrenia (ITAREPS) (Komatsu et al, 2013; Spaniel et al, 2012; Spaniel, Vohlidka, Hrdlicka, et al, 2008; Spaniel, Vohlidka, Kozeny, et al, 2008), and a trial of an online platform for self-managing bipolar disorder (Todd et al, 2014). Measures of feasibility and acceptability included frequency of intervention use over time, response rates, study retention, proportion of devices that were returned undamaged, and participant reported usability (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Among these were 4 modified versions of the Health Buddy automated home messaging device delivered across diverse mental health settings (Godleski et al, 2012; Kasckow et al, 2011; Pratt et al, 2013; Pratt et al, 2014), 3 separate evaluations of the Information Technology Aided Relapse Prevention Programme in Schizophrenia (ITAREPS) (Komatsu et al, 2013; Spaniel et al, 2012; Spaniel, Vohlidka, Hrdlicka, et al, 2008; Spaniel, Vohlidka, Kozeny, et al, 2008), and a trial of an online platform for self-managing bipolar disorder (Todd et al, 2014). Measures of feasibility and acceptability included frequency of intervention use over time, response rates, study retention, proportion of devices that were returned undamaged, and participant reported usability (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14][15] It is well established in adult medical and surgical inpatient settings that psychiatric services are effective for responding to troubling mental health symptoms, 6,9 are well received by patients and referring medical services, and contribute to staff education about psychiatric illness and management. [16][17][18][19][20] PCLS involvement has been found to reduce medical complications, length of stay, and number of hospitalizations via early referral for psychiatric consultations, 21 behavioral health interventions (cognitivebehavioral or supportive therapies), 22,23 treatment of psychiatric presentation on medical and surgical units (ie, delirium, depression), 10,21 and facilitating access to appropriate psychiatric treatment postdischarge.…”
mentioning
confidence: 99%
“…More than 70 different outcome measures were used in these studies, ranging from self-report to biological measures. Self-management skills and behaviors significantly increased in seven studies (2225,28,32,33). Self-management attitudes significantly increased in four studies (25,26,28,32) and one study reported qualitative evidence of increased self-management attitudes (35).…”
Section: Resultsmentioning
confidence: 99%
“…The 15 included studies reported on nine interventions (Table 1), including: Automated Telehealth (22); Health and Recovery Peer program (HARP) (23); Helping Older People Experience Success (HOPES) (2426); Integrated Illness Management and Recovery (I-IMR) (27,28); Life Goals Collaborative Care (LGCC) (2931); Living Well (32); Norlunga Chronic Disease Self-Management program (33); Paxton House (34); and Targeted Training in Illness Management (TTIM) (35,36) (Table 1). Interventions were studied within diverse types of settings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation